(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses the practice of venerating graves and mausoleums, which have become special places of worship for Muslims in Uzbekistan. The authors also cite historical evidence of the presence of tugs with horse tails on the graves of spiritual leaders and explain their symbolic meaning. The research conducted in this area is described, as well as the points of view of various authors on the historical and functional significance of these tugs are presented.